Antiphospholipid (Hughes) syndrome: description of population and health-related quality of life (HRQoL) using the SF-36. (February 2015) - Georgopoulou, S; Efraimidou, S; MacLennan, S J; Ibrahim, F; Cox, T
Objective: Antiphospholipid (Hughes) syndrome (APS) affects mainly women 15 to 50 years of age and is responsible for approximately 20% of strokes in people <40 years. Little is known about the psychological burden of this long-term condition. We investigated HRQoL in APS. Methods: We conducted a cross-sectional survey involving 270 members of the Hughes Syndrome Foundation worldwide. Data included HRQoL (SF-36), demographics, and APS-related self-reported major issues. Response rate was 60%. Results: T-tests indicated significantly worse mean scores for seven of the eight domains of the SF-36 in secondary antiphospholipid syndrome (SAPS) compared to primary antiphospholipid syndrome (PAPS), e.g. bodily pain t(263) = 6.10 p  < 0.001 except for mental health t(267) = 1.95 p  = 0.053. PAPS appeared to be associated with poorer HRQoL in most mental health domains but overall better physical domains compared to systemic lupus erythematosus (SLE) alone. SAPS appeared to have a more adverse impact on HRQoL compared to PAPS and SLE. Major issues identified: pain and fatigue, lack of health care professional/public awareness, and medication unpredictability. Conclusion: HRQoL in PAPS appears to be generally better than SLE and SAPS in physical domains, but poorer in mental domains. APS patients might need more social support in terms of information and awareness of the condition to improve their coping strategies.